Antigen-Specific Regulatory T Cells and Low Dose of IL-2 in Treatment of Type 1 Diabetes - Pham, Minh N.; von Herrath, Matthias G.; Vela, Jose Luis (Frontiers in Immunology, 2016)
Regulatory T cells (Tregs) play an important role in preventing effector T-cell (Teff) targeting of self-antigens that can lead to tissue destruction in autoimmune settings, including type 1 diabetes (T1D). Autoimmunity is caused in part by an imbalance between Teff and Tregs. Early attempts to treat with immunosuppressive agents have led to serious side effects, thus requiring a more targeted approach. Low-dose IL-2 (LD IL-2) can provide immunoregulation with few side effects by preferentially acting on Tregs to drive tolerance. The concept of LD IL-2 as a therapeutic approach is supported by data in mouse models where autoimmunity is cured and further strengthened by success in human clinical studies in hepatitis C virus-induced vasculitis, chronic graft-versus-host disease, and Alopecia areata. Treatment will require identification of a safe therapeutic window, which is a difficult task given that patients are reported to have deficient or defective IL-2 production or signaling and have experienced mild activation of NK cells and eosinophils with LD IL-2 therapy. In T1D, an LD IL-2 clinical trial concluded that Tregs can be safely expanded in humans; however, the study was not designed to address efficacy. Antigen-specific therapies have also aimed at regulation of the autoimmune response but have been filled with disappointment despite an extensive list of diverse islet antigens tested in humans. This approach could be enhanced through the addition of LD IL-2 to the antigenic treatment regimen to improve the frequency and function of antigen-specific Tregs, without global immunosuppression. Here, we will discuss the use of LD IL-2 and islet antigen to enhance antigen-specific Tregs in T1D and focus on what is known about their immunological impact, their safety, and potential efficacy, and need for better methods to identify therapeutic effectiveness.